Induction of Humoral and Cellular Immunity by Intradermal Delivery of SARS-CoV-2 Nucleocapsid Protein Using Dissolvable Microneedles - Chaiyaporn Kuwentrai; Jinming Yu; Bao-zhong Zhang; Ye-fan Hu; Ying Dou; Hua-rui Gong; Jian-Dong Huang; Chenjie Xu (Journal of Immunology Research)
The nucleocapsid protein (NP) of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) contains immunogenic epitopes that can induce cytotoxic T lymphocyte (CTL) against viral infection. This makes the nucleocapsid protein a suitable candidate for developing a vaccine against SARS-CoV-2 infection. This article reports the intradermal delivery of NP antigen using dissolvable microneedle skin patches that could induce both significant B cell and T cell responses.